SMAIZER (SMART AGILITY SPEED ANALYZER) INNOVATION SHADOW EXERCISE TOOL IN INCREASING ATHLETE DISCLOSURE - Haikal Fikri Abdi Rachman; Yosha Dima Distya; Anita Wahyuningtias; Agung Prijo Budijono (Journal of International Conference Proceedings (JICP), 2018)
The Purpose The purpose of this study is to provide solutions to the problems of effective and efficient footwork of athletes to facilitate athletes move the field so as to minimize the stamina and energy required. The Methodmethod used is to utilize Microcontroller in shadow Exercise tool to overcome the footsteps are not uniform. which comes with a special software that serves as a data storage exercise (exercise history). Results The expected result is to know a quantitative increase in agility of a player during practice, so that all trainers can evaluate accurately and obtain clear data. The Findings finding of this study are the use of Microcontroller with special Software as an effective and efficient athlete foot problem solution, on improving the agility of a player quantitatively is very influential when all trainers evaluate the exercises in which the process is still using qualitative assessment. Keywords :Smaizer, Microcontroller, Exercise shadows, atheletes